Guest Editorial Introduction to the Special Issue on Advances in Clinical and Health-Care Knowledge Management. - Bali, R.K.
Clinical and health-care knowledge management (KM) as a discipline has attracted increasing worldwide attention in recent years. The approach encompasses a plethora of interrelated themes including aspects of clinical informatics, clinical governance, artificial intelligence, privacy and security, data mining, genomic mining, information management, and organizational behavior. This paper introduces key manuscripts which detail health-care and clinical KM cases and applications.
Keywords: Clinical management; Health-care informatics; Knowledge management (KM).